Method for demarcating gas engine knocking - SHI LIANG; SUN WANCHAO; DUAN JIXIANG (2017)
The invention discloses a method for demarcating gas engine knocking. The method comprises two major steps of demarcating a knocking threshold value and controlling vehicle knocking. Whether an engine of the invention knocks is judged through comparison between the knocking threshold obtained through a knocking experiment and a ratio of a vehicle knocking signal to vehicle environment noise measured in practical running environment of the engine. Participation of the practical running environment of the engine is added in judging processing, so that effect of environment of judgment of the engine knocking can be well reduced, adaptability of the engine is better, and misjudgment rate of the knocking is reduced 本发明公开了种燃气发动机爆震标定方法，包括标定爆震阀值和车辆爆震控制两大步，本发明的发动机是否爆震，根据爆震实验中，得出的爆震阀值与发动机实际运行环境中测算出来的车辆爆震信号/车辆环境噪声比值进行比较判定，在判断过程中，增加了发动机实际运行环境的参与，这样可以很好地降低环境对发动机爆震判断的影响，使发动机适应性更强，爆震误判率降低。